Meta-synthesis analysis of costs and benefits in general and Higher education - ahmad keykha (Allameh Tabataba'i University Press, 2018)
Education systems (public and higher) play a key role in the comprehensive development of diverse ecosystems, but in recent decades, with increasing turbulence and global financial crises, governments have lacked funding to provide education. Higher education budget deficits have become increasingly important. This has made it imperative to pay more attention to evaluating the performance of educational units to improve their financial resources to increase their efficiency and effectiveness. Therefore, using this qualitative method, in particular, the cross-cutting strategy seeks to answer two questions: 1) What are the categories and concepts of content analysis and content analysis strategy with the educational system? Can these concepts and categories be presented to improve the status of the education system? Succeeded. In the first question, for the first question, there were five sub-categories: governance, management-executive, welfare, consequence, educational system. In the second question, corresponding to each of these categories, the status of the educational system was criticized and then the policies proposed.